[CaL3][Co(NCS)4] – potential agent for enhancing the productivity of Chlorella Vulgaris Beijer. microalga - Boris Nedbaliuc; Eugeniu Ciobanu; Sofia Grigorcea; Dumitru Ureche; Eduard Coropceanu; Lilia Brînză (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The advancing of modern biotechnologies requires the development of new procedures for stimulating the biological activity of some cultures that produce substances of vital importance. Coordination compounds present an effective solution for achieving this objective. The inclusion of some biometals in the composition of the coordination compounds, as well as some organic ligands with electron-donating atoms, creates premises for the assembly of molecules that can influence biological systems. The productivity of the microalgae Chlorella vulgaris Beijer., cultivated on modified nutrient media and supplemented with a coordination compound containing calcium, was evaluated. It was found that increased concentrations of this compound have an inhibitory action on Chlorella strain. A stimulatory effect was registered when the concentrations of 10 mg/L, 5 mg/L and 1 mg/L of the tested coordination compound were administered, the biomass obtained was higher by 10.8%, 7.6% and 5.4% in relation to the control group.